Estimates of heritability for alometric condition factor from 90 to 330 days in curimbatá - Rocha, Marco Antonio da; Ribeiro, Edson Luis de Azambuja; Mizubuti, Ivone Yurika; Silva, Leandro das Dores Ferreira da (Semina: Ciências Agrárias, 2000)
1 PROBLEMA<!–[if gte mso 9]> Papelaria Dinossauro 10.2625 <![endif]–><!–[if gte mso 9]> Normal 0 21 MicrosoftInternetExplorer4 <![endif]–> <!– /* Font Definitions */ @font-face font-family:Verdana; panose-1:2 11 6 4 3 5 4 4 2 4; mso-font-alt:Verdana; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:536871559 0 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The relation between body weight and body length can be used to calculate the condition factor in fish. This factor express the grade of development of the fish. A sample of 253 fish from a hierarchial mating (5 females and 10 males) were used. Fishes were kept in net cages until, 150 days of age, and then marked and transferred to three tanks of I00m2/each; where they stayed until 330 days of age. The fishes were fed with a 30% crude protein and 2800 kcal/kg of metabolizable energy ration. Heritabilities of the alometric condition factor, from ages 90 to 300 days, were estimated using a model including female and mate within female. Heritabilities calculated from sire components of variance were: 0,28 Â± 0,20; 0,11 Â± 0,16; 0,24 Â± 0,22: 0.20 Â±0,19: 0,19 Â± 0,19. respectively to 90, 150, 210. 270 and 330 days of age. These values suggest a small expected genetic gain from selection for this trait.